Fecal microbiota transplantation treatment of autoimmune-mediated type 1 diabetes mellitus - He, Lina; Chen, Rongping; Zhang, Bangzhou; Zhang, Shuo; Khan, Barkat Ali; Zhu, Dan; Wu, Zezhen; Xiao, Chuanxing; Chen, Baolong; Chen, Fengwu; Hou, Kaijian (Frontiers in Immunology, 2022)
Type 1 diabetes mellitus (T1DM) is an autoimmune-mediated disease characterized by a reduced or absolute lack of insulin secretion and often associated with a range of vascular and neurological complications for which there is a lack of effective treatment other than lifestyle interventions and pharmacological treatments such as insulin injections. Studies have shown that the gut microbiota is involved in mediating the onset and development of many fecal and extrafecal diseases, including autoimmune T1DM. In recent years, many cases of gut microbiota transplantation for diseases of the bowel and beyond have been reported worldwide, and this approach has been shown to be safe and effective. Here, we conducted an experimental treatment study in two adolescent patients diagnosed with autoimmune T1DM for one year. Patients received one to three rounds of normal fecal microbiota transplants (FMT) and were followed for up to 30 weeks. Clinical outcomes were measured, including biochemical indices, medication regimen, and dosage adjustment. Fecal microbiota metagenomic sequencing after transplantation provides a reference for more reasonable and effective microbiota transplantation protocols to treat autoimmune T1DM. Our results suggest that FMT is an effective treatment for autoimmune T1DM. Clinical Trial Registration http://www.chictr.org.cn, identifier ChiCTR2100045789.